Improved dialytic removal of protein-bound uremic toxins by intravenous lipid emulsion in chronic kidney disease rats. Issue 11 (9th May 2019) - Shi, Yuanyuan; Zhang, Yumei; Tian, Huajun; Wang, Yifeng; Shen, Yue; Zhu, Qiuyu; Ding, Feng
Abstract: Background: Protein-bound uremic toxins (PBUTs) have received extensive attention, as their accumulation leads to pleiotropic toxic biological effects, while the removal of these solutes by conventional dialysis therapies is severely hampered. This study aimed to examine whether increased removal of PBUTs could be achieved with intravenous lipid emulsion (ILE). Methods: PBUTs such as 3-carboxy-4-methyl-5-propyl-2-furanpropionic acid (CMPF), p -cresyl sulfate (PCS) and indoxyl sulfate (IS) were spiked with human serum albumin (HSA) solution and the inhibitory effects of free fatty acid (FFA) on the binding of CMPF, PCS and IS to HSA were examined separately in vitro by ultrafiltration. In vitro dialysis of albumin solution was then performed to investigate the effects of fatty acid (FAs) mixtures infusion on the fractional removal of PBUTs. Finally, the inhibitory effect of FFA on the binding of PBUTs to albumin was examined in uremic rats, and blood purification therapy was conducted to calculate the reduction ratio (RR) and the total solute removal (TSR) of solutes. Results: The percentage protein binding of CMPF, PCS and IS decreased significantly with increasing FFAs concentrations, and the inhibitory effect was more remarkable with the addition of oleic acid or linoleic acid than that of eicosapentaenoic acid and docosahexaenoic acid. In vitro infusion of FAs increased the fractional removal of CMPF to 14.40 ± 2.38%. PCS, IS and indole-3-acetic acid removal increased from 8.00 ± 2.43%, 11.68 ± 1.54% and 15.38 ± 3.97%, respectively, at baseline to 28.21 ± 5.99%, 35.42 ± 5.27% and 40.18 ± 5.05%, respectively, when FAs were present. In vivo, rat serum concentrations of free PBUTs were significantly higher in the ILE group than in the control group, and administration of ILE resulted in higher RRs and more TSR for PBUTs after 3 h of hemodialysis (HD) therapy compared with the control group. Conclusions: Administration of ILE effectively increased the dialytic removal of PBUTs. This method could be applied to current HD therapy.